Eddy Current Probability of Detection for Mid-Bore and Corner Cracks in Bolt Holes of Service Material. Issue 1 (2nd January 2016) - Underhill, P. Ross; Krause, Thomas W.
Abstract : Fatigue cracks are prone to develop around fasteners found in multilayer aluminum structures on aging aircraft. Probability of detection (POD) studies using eddy current techniques within the bolt holes contribute to risk assessments used in evaluating the serviceability of these aircraft. Signal response to corner and mid-bore cracks by eddy current testing using standard split-D differential probes has been examined for in-service material from the horizontal stabilizer of a Hercules aircraft. Results are compared to data obtained from laboratory samples with drilled holes. Based on a logistic regression analysis, the results show no significant difference for a90/95 (90% of the cracks of size a will be detected 95% of the time) for mid-bore crack length of 0.60 mm in this study compared to 0.62 mm in earlier work on drilled holes. However, there was a substantial loss of sensitivity for corner cracks. In this study on in-service material, the a90/95 for corner cracks was 0.82 mm compared to 0.31 mm obtained from drilled holes. Decrease in sensitivity was attributed to damage at the hole's corners of the in-service material, including rounding, folded metal, and burrs. Hole damage also significantly increased the risk of a false call.